A conjugate gradient method with descent properties under strong Wolfe line search - Mustafa, Mamat; Zull, N; Aini, N.; Shoid, S.; Ghani, N.H.A.; Mohamed, N.S.; Rivaie, M; Mamat, M. (2017)
The conjugate gradient (CG) method is one of the optimization methods that are often used in practical applications. The continuous and numerous studies conducted on the CG method have led to vast improvements in its convergence properties and efficiency. In this paper, a new CG method possessing the sufficient descent and global convergence properties is proposed. The efficiency of the new CG algorithm relative to the existing CG methods is evaluated by testing them all on a set of test functions using MATLAB. The tests are measured in terms of iteration numbers and CPU time under strong Wolfe line search. Overall, this new method performs efficiently and comparable to the other famous methods.